Representation of Islam and Muslims in the Australian Newspapers: Exploring the Predominant Discourses - Dr. Salma Umber; Ghauri, Dr. Muhammad Junaid (Journal of Islamic Thought and Civilization, 2020)
This paper is an endeavor to explore the predominant discourses in the editorial representation of Islam and Muslims by selected Australian newspapers from November 01, 2016 to March 31, 2017. Making use of the lexicalization and ideological square strategies proposed by Teun A. van Dijk, the researcher examined the editorial coverage of two Australian newspapers namely The Age and The Australian. According to the results, the editorial discourse regarding Islam and Muslims in both dailies was entirely opposite to each other. The Australian portrayed Islam and Muslims negatively by producing a ‘securitized’ and ‘Othered’ image of ‘Them’, within and outside Australia’s boundaries. On the contrary, The Age created a significant ‘counter discourse’ on Islam and Muslims by portraying them positively and as victims. The explicit impact of right-left ideological lines of the selected newspapers was found evident in their editorial discourses regarding Islam and Muslims.